Quantifying transboundary transport flux of CO over the Tibetan Plateau: variabilities and drivers - Z. Sun; H. Yin; Z. Pan; C. Li; X. Lu; K. Liu; Y. Sun; Y. Sun; C. Liu; C. Liu; C. Liu; C. Liu (Atmospheric Chemistry and Physics)
The Tibetan Plateau significantly impacts regional and global climate systems due to its unique geographical location and complex environmental processes. This study investigates the variability and driving force of transboundary transport flux of carbon monoxide (CO) over the Tibetan Plateau from May 2018–April 2024. The CO fluxes were calculated with a closed-loop integral method using the TROPOMI, ERA5, and GEOS-CF data products. The results show that the external influx and internal efflux of CO over the Tibetan Plateau in each year are relatively close and have similar seasonal characteristics. High levels of CO flux occur in late autumn to winter, and low levels occur in summer. In most cases, CO flux maximizes in November, December, or January and minimizes in July or August. The month-to-month variability during late autumn to winter is greater than that in summer. The Tibetan Plateau has experienced an increase of 2.86 Tg CO yr−1 in external influx, while the internal efflux has slightly decreased by -1.70<mspace linebreak="nobreak" width="0.125em"/>Tg<mspace width="0.125em" linebreak="nobreak"/>CO<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="83pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="7332a9d0e3e467d46eccb7681ee1c54c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6823-2025-ie00001.svg" width="83pt" height="15pt" src="acp-25-6823-2025-ie00001.png"/></svg:svg>. The magnitude of the increase in external influx in the southwestern segment is greater than in the northeastern segment. Conversely, the magnitude of the decrease in internal efflux in the northeastern segment is greater than in the southwestern segment. The source attribution results reveal that the external input of CO into the Tibetan Plateau mainly comes from South Asia. The increase in external influx of CO in recent years over the Tibetan Plateau is potentially linked to the rapid rise in CO concentrations from South Asia.